Controlling Nonlinear Dynamics of Milling Bodies in Mechanochemical Devices Driven by Pendular Forcing - Polo, A.; Carta, M.; Delogu, F.; Rustici, M.; Budroni, M. A. (Frontiers in Chemistry, 2022)
Understanding the dynamics of milling bodies is key to optimize the mixing and the transfer of mechanical energy in mechanochemical processing. In this work we present a comparative study of mechanochemical reactors driven by harmonic pendular forcing and characterized by different geometries of the lateral borders. We show that the shape of the reactor bases, either flat or curved, along with the size of the milling body and the elasticity of the collisions represent relevant parameters that govern the dynamical regimes within the system and can control the transition from periodic to chaotic behaviors. We single out possible criteria to preserve target dynamical scenarios when the size of the milling body are changed, by adapting the relative extent of the spatial domain. This allows to modulate the average energy of the collisions while maintaining the same dynamics and paves the way for a unifying framework to control the dynamical response in different experimental conditions. We finally explore the dynamical and energetic impact of an increasingly asymmetric mechanical forcing.